Maternal dietary diversity and its correlates in a semi-urban municipality of Nepal: A cross-sectional study - Reshika Rimal; Ayusha Rimal; Pranil Man Singh Pradhan (PLOS Global Public Health, 2026)
Maternal dietary diversity is vital for the health of both mothers and children during lactation, yet it is often compromised in low- and middle-income countries. This cross-sectional study among 251 lactating mothers in Tarakeswor Municipality, Nepal, assessed dietary diversity using a 24-hour dietary recall and the Minimum Dietary Diversity for Women (MDD-W) indicator. Overall, 68.1% of mothers achieved the minimum dietary diversity (≥5 of 10 food groups), with a mean score of 5.03 ± 1.25. In multivariable analysis, higher odds of meeting MDD were observed among mothers with secondary or higher education (aOR = 7.5; 95% CI: 3.8–15.0), employment (aOR = 2.9; 95% CI: 1.4–5.8), joint or extended family structure (aOR = 3.7; 95% CI: 1.9–7.0), the highest wealth quintile (aOR = 4.2; 95% CI: 1.9–9.1), food-secure households (aOR = 4.5; 95% CI: 2.3–7.9), adequate nutrition knowledge (aOR = 5.2; 95% CI: 2.7–9.8), ≥ 4 antenatal care visits (aOR = 1.9; 95% CI: 1.0–3.4), and higher empowerment (aOR = 3.9; 95% CI: 1.9–7.8). These findings highlight substantial socioeconomic disparities in maternal dietary diversity and underscore the need for integrated, equity-focused nutrition interventions in rapidly urbanizing settings in low- and middle-income countries. These findings can inform targeted maternal nutrition programs in semi-urban municipalities of Nepal by prioritizing nutrition education, improving household food security, and integrating dietary diversity counseling into antenatal and postnatal care services.